Measuring change in employment characteristics: the effects of dependent interviewing - Emanuela Sala; Peter Lynn (University of Essex, Institute for Social and Economic Research (ISER), 2004)
Subsequently published as Lynn, Peter, Sala, Emanuela (2006) Measuring change in employment characteristics: the effects of dependent interviewing, International Journal of Public Opinion Research, Oxford University Press. 18(4) Win., 500-509
Keywords: 330